White Fire - Oxenham, John, 1852-1941; Manton, G. Grenville (George Grenville), 1855-1932 (Salt Lake City, UT : Project Gutenberg, 2011)
"White Fire" by John Oxenham is a novel written in the early 20th century. The story revolves around the characters Jean Arnot, a wealthy and inquisitive young woman, and Kenneth Blair, an aspiring missionary eager to serve in the South Seas. As their paths cross, themes of love, sacrifice, and the pursuit of purpose begin to unfold, making the narrative rich in both emotional depth and moral dilemmas. At the start of the novel, readers are introduced to a thirteen-year-old Jean, who is embarking on an adventure near her home, where she encounters Kenneth, a herd-laddie with dreams of becoming an explorer. Their innocent interaction is marked by a budding curiosity and admiration, laying the groundwork for their future. As time passes, we learn about Jean's evolution into a wealthy young woman who seeks fulfillment in her life. After a dramatic meeting where Kenneth speaks of his missionary aspirations, Jean's feelings for him intensify, leading her to a bold decision that intertwines her fate with his. The opening section skillfully sets the stage for the exploration of their intertwined destinies and the challenges they will face together. (This is an automatically generated summary.)
Release date is 2011-11-19
Produced by Al Haines
Keywords: Missionaries -- Fiction; British -- Oceania -- Fiction